2016
DOI: 10.1111/1750-3841.13374
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sequential Environmental and Harvest Stressors on the Sensory Characteristics of Cultured Channel Catfish (Ictalurus Punctatus) Fillets

Abstract: Stress during fish culture alters physiological homeostasis and affects fillet quality. Maintenance of high-quality seafood is important to ensure the production of a marketable product. This study assessed how sequential stressors affect the sensory and quality characteristics of catfish (Ictalurus punctatus) fillets. Three stress trials were conducted where temperature (25 or 33 °C) and dissolved oxygen (DO, approximately 2.5 or >5 mg/L) were manipulated followed by socking and transport stress. After each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…As precooked food products are generally stored frozen, assuring product quality is a major challenge encountered by the provider (Pie et al, 1991;Ciaramella et al, 2016). Food and its products may deteriorate during frozen storage as a consequence of dehydration, protein denaturation, lipid peroxidation or tissue cell breakage.…”
Section: Introductionmentioning
confidence: 99%
“…As precooked food products are generally stored frozen, assuring product quality is a major challenge encountered by the provider (Pie et al, 1991;Ciaramella et al, 2016). Food and its products may deteriorate during frozen storage as a consequence of dehydration, protein denaturation, lipid peroxidation or tissue cell breakage.…”
Section: Introductionmentioning
confidence: 99%
“…Borderías and Sánchez‐Alonso () proposed that seafood species including wild and farmed fish can undergo physiological stress due to changes in environmental and preharvest conditions. Although the report by Borderías and Sánchez‐Alonso () did not include observations under frozen storage conditions, some authors believe that changes in environmental and preharvest conditions can impact the sensory properties and overall acceptability of seafood products (Ciaramella, Kim, Avery, Allen, & Wes Schilling, ). Like other seafood species, lobsters are not exempt from environmental stresses.…”
Section: Resultsmentioning
confidence: 99%
“…However, exposure to extreme poor water quality conditions resulted in only one red fillet, while two red fillets occurred in the treatment more typical of normal pond conditions (typical treatment). Notably, prior research has not produced similar red fillets as those observed by catfish processors (Allred et al, ) through simulated poor water quality during hauling procedures (Bosworth et al, ) nor chronic exposure to poor water quality followed by harvest procedures (Ciaramella, Kim, et al, ). When considering these experiments along with the results of this study, red fillets are not directly caused by poor water quality and handling stress.…”
Section: Discussionmentioning
confidence: 98%
“…Although harvesting procedures have been standardized for efficient fish removal and transport to processors, parts of the procedure, namely seining, socking and hauling, create conditions known to induce physiological stress in fish (Bosworth, Small, & Mischke, ; Ciaramella, Kim, Avery, Allen, & Schilling, ; Ciaramella, Nair, Suman, Allen, & Schilling, ; Fauconneau & Laroche, ; Fries, Berkhouse, Morrow, & Carmichael, ; Harmon, ; Pfeiffer & Freeman, ; Torrans, Hogue, & Pilkinton, ). Seining is the first step of a harvest and involves pulling large seine nets with tractors across the pond, a practice that has undergone minimal change since its development in the 1960s (Torrans et al, ; Trimpey, Engle, Heikes, Davis, & Goodwin, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation